Investigating Students’ Difficulties in Understanding Confidence Intervals in Linear Regression Models - Rashidah Paujah @ Ismail, Nor; Abdol Razak, Fadzilah; Baharun, Norhayati (International Journal of Engineering and Technology, 2018)
How do tertiary students perform when finding confidence intervals of linear regression models? Do they have strong understanding on how to compute the interval and provide good explanation on the interval obtained? To answer these questions, 197 answer scripts were examined to investigate students’ ability to calculate the confidence interval of the regression slope and their ability to make comprehensive interpretation afterwards. It was found that only 48% of the students managed to compute the confidence interval correctly. The errors made by most of the students were caused by the failure to identify the correct degrees of freedom and the failure to evaluate the correct value of the standard error of the slope. Of those who were able to compute the correct values, the percentage that were able to give complete and correct interpretation dropped to only 7.1%. 68.5% of them provided incorrect interpretations which showed their inability to understand the concept of regression slope. It is hoped that this study will give some ideas to educators in providing better understanding on computing and interpreting the confidence interval among students.